The Influence Of Pet Influencer @Kiwibritishcat On The Image Of The Metro Jaya Police Human Resources Bureau - Khalisa, Nadine Nur; Rachim, Widya Natassha; Kampf, Constance (Jurnal Mamangan, 2024)
In the rapidly developing world of public relations. The way to spread awareness of a brand is by doing endorsements. Endorsers who were previously actresses, athletes and public figures, have now been found "pet influencers" as supporters. Uniquely, the police institution uses the services of "pet influencer" supporters. The purpose of this study is to see if there is an influence of the use of pet influencer supporters on the police institution. This study was designed as an analytical study related to the hypothesis that connects the correlation and significance between the independent variable (pet influencer) with the dependent variable (image) of the Human Resources Bureau of the Metro Jaya Police regarding the existence of idols in society. To find the answer, some data are needed that need to be tested for significance and validity. Therefore, this work uses validity and reliability tests. To analyze the hypothesis, this study uses simple linear regression analysis Anova, Coefficient, and T Test (Partial Parameter Significance) and Correlation Coefficient Test. This work also uses the Instagram platform as a basis for thinking that is the hypothesis in this work. Based on the simple linear regression test in the Coefficients table, the significance value of Music Video is 0.000 <0.05, so the novelty of this study is that Pet Influencers, which in this study are positioned as independent variables (X), are proven to be valid and reliable in influencing the Image of the Metro Jaya Police Human Resources Bureau, which in this study is positioned as dependent variables (Y).